Palm tocotrienol-rich fraction improves vascular proatherosclerotic changes in hyperhomocysteinemic rats - Ku Zaifah, Norsidah; Ayob, Azizi; Yusuf, Ahmad Asmadi; Yusuf, Kamisah; Othman, Faizah (Hindawi Publishing, 2013)

(untitled)
Palm Tocotrienol-Rich Fraction Improves Vascular Proatherosclerotic Changes in Hyperhomocysteinemic Rats Author(s): Norsidah, KZ (Norsidah, Ku-Zaifah)[ 1 ] ; Asmadi, AY (Asmadi, Ahmad Yusof)[ 2 ] ; Azizi, A (Azizi, Ayob)[ 3 ] ; Faizah, O (Faizah, Othman)[ 4 ] ; Kamisah, Y (Kamisah, Yusof)[ 5 ] Source: EVIDENCE-BASED COMPLEMENTARY AND ALTERNATIVE MEDICINE Article Number: 976967 DOI: 10.1155/2013/976967 Published: 2013 Times Cited: 0 (from Web of Science) Cited References: 58 [ view related records ] Citation Map Abstract: This study investigated the effects of palm tocotrienol-rich fraction (TRF) on aortic proatherosclerotic changes in rats fed with a high methionine diet. Forty-two male Wistar rats were divided into six groups. The first group was the control (fed with a basal diet). Another five groups were fed with 1% methionine diet for 10 weeks. From week 6 onward, folate (8mg/kg diet) or palm TRF (30, 60, and 150mg/kg diets) was added into the diet of the last four rat groups, respectively. The high methionine diet raised the plasma total homocysteine and aortic lipid peroxidation, which were reduced by the palm TRF and folate supplementations. Plasma nitric oxide was reduced in the high methionine group compared to the control (3.72 +/- 0.57 versus 6.65 +/- 0.53 mu mol/L, P < 0.05), which reduction was reversed by the palm TRF (60 and 150mg/kg) and folate supplementations. The increased aortic vascular cell adhesion molecule-1 expression in the methionine group (2.58 +/- 0.29) was significantly reduced by the folate (1.38 +/- 0.18) and palm TRF at 150mg/kg (1.19 +/- 0.23). Palm TRF was comparable to folate in reducing high methionine diet-induced plasma hyperhomocysteinemia, aortic oxidative stress, and inflammatory changes in rats